Ed Ricketts and Friends - Unknown:::Creator::::::::::::
Ed 'Doc' Ricketts standing with two women on his right, and a man and woman on his left. The two people on the outsides are playing guitar. From Left to right: Peggy Cliff, Toni Jackson, Ed Ricketts, Francis Strong, Toby Street. Toni Jackson lived with Ed. Ricketts for seven years. Toby Street met Steinbeck while both attended Stanford.